PELAKSANAAN BIMBINGAN KARIR UNTUK MENINGKATKAN MINAT MELANJUTKAN STUDI SISWA SMA NEGERI 1 MURATARA - Defriansyah, Dedi; Hartini, Hartini; Rizal, Syamsul (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2023)
Abstract: Low career maturity among students has become a critical issue in the realm of education, indicating students' lack of confidence in their career choices and their ability to plan a suitable future. This research aims to evaluate the implementation of career guidance programs at State High School 1 Muratara, specifically focusing on efforts to enhance students' interest in studies through group counseling sessions. A qualitative approach was employed in this study, involving interviews, observations, and document analysis as data collection methods. To ensure data validity, a triangulation of sources technique was utilized, involving interviews with the Guidance Counselor, students, and subject teachers prior to the provision of career information services. The research findings revealed that initially, 4 participants exhibited low levels of career maturity, but after receiving career information services, the number of participants reaching a better level of career maturity increased to 7. This research confirms that the implementation of career guidance through career information services at the school has significantly positively impacted the improvement of students' study interests. Key success factors in this program included strong support from guidance and counseling teachers, effective collaboration with relevant parties, and the optimization of available resources. However, a challenge identified was the lack of motivation among participants to engage in career information services. This research contributes significantly to deepening the understanding of career guidance practices in the school environment, emphasizing the importance of enhancing students' study interests as a key factor in developing their potential and making appropriate career choices. The research findings were generated through qualitative data analysis using a Theme Grouping approach, focusing on evaluating the implementation of the career guidance program through career information services at State High School 1 Muratara.Keywords: Career; Guidance; Boosting Interest; Student.Abstrak: Kematangan karir siswa yang rendah telah menjadi isu kritis dalam ranah pendidikan, mengindikasikan ketidakyakinan siswa terhadap pilihan karir mereka dan kemampuan mereka untuk merencanakan masa depan yang sesuai. Penelitian ini memiliki tujuan untuk mengevaluasi pelaksanaan program bimbingan karir di SMA Negeri 1 Muratara dengan fokus khusus pada upaya meningkatkan minat studi siswa melalui sesi bimbingan kelompok. Pendekatan kualitatif digunakan dalam penelitian ini, yang mencakup wawancara, observasi, dan analisis dokumen sebagai metode pengumpulan data. Untuk memastikan keabsahan data, teknik triangulasi sumber digunakan, dengan melibatkan wawancara dengan Guru BK, siswa, dan guru mata pelajaran sebelum pemberian layanan informasi karir. Hasil penelitian mengungkapkan bahwa sebanyak 4 peserta didik awalnya menunjukkan tingkat kematangan karir yang rendah, namun setelah menerima layanan informasi karir, jumlah peserta didik yang mencapai tingkat kematangan karir yang lebih baik meningkat menjadi 7 peserta didik. Hasil penelitian ini menegaskan bahwa pelaksanaan bimbingan karir melalui layanan informasi karir di sekolah telah memberikan dampak positif yang signifikan pada peningkatan minat studi siswa. Faktor-faktor kunci dalam kesuksesan program ini meliputi dukungan yang kuat dari guru bimbingan dan konseling, kerjasama yang efektif dengan pihak-pihak terkait, serta optimalisasi sumber daya yang tersedia. Namun, kendala yang muncul adalah kurangnya motivasi peserta didik dalam mengikuti layanan informasi karir. Penelitian ini memberikan kontribusi penting dalam memperdalam pemahaman tentang praktik bimbingan karir di lingkungan sekolah dan menekankan pentingnya peningkatan minat studi siswa sebagai faktor kunci dalam pengembangan potensi mereka dan pemilihan karir yang tepat. Hasil penelitian ini dihasilkan melalui analisis data kualitatif dengan pendekatan Pengelompokan Tema dan berfokus pada evaluasi pelaksanaan program bimbingan karir dengan layanan informasi karir di SMA Negeri 1 Muratara.Kata Kunci: A. Bimbingan; Karir; Meningkatkan Minat; Siswa.